P614NLRP3 inflammasome as a sensor of metabolic stress in cardiac fibroblasts. (15th July 2014) - Sokolova, M; Vinge, LE; Alfsnes, K; Ohm, IK; Bliksoen, M; Sandanger, Ø; Aukrust, P; Ranheim, T; Yndestad, A
Abstract: Purpose: Type 2 diabetes (T2D) is an important risk factor for heart failure. T2D is associated with the metabolic syndrome, encompassing cardiovascular risk factors such as obesity, insulin resistance and dyslipidemia, factors also associated with left ventricular diastolic dysfunction. Patients with T2D have elevated plasma levels of free fatty acids and these are proposed to activate inflammation. Interleukin-1β (IL-1β) is activated by the NLRP3 inflammasome and a central mediator in T2D. Palmitate, the most abundant saturated fatty acid in plasma was recently shown to activate the NLRP3 inflammasome in macrophages. The aim of this study was to investigate if this mechanism operates within myocardial cells. Methods and Results: We first replicated previous findings by incubating bone marrow-derived macrophages with palmitate, and found release of active IL-1β. We went on to study primary mouse cardiac fibroblasts (CF). CF were stimulated with LPS, causing priming of the inflammasome, and then with palmitate. This caused release of active IL-1β. Importantly, this was not found in CF from NLRP3 and ASC deficient mice, demonstrating that the effect of palmitate on IL-1β release is mediated through the NLRP3 inflammasome. Other fatty acids such as eicosapentaenoic acid (EPA), oleic acid (OA), docosahexaenoic acid did not cause inflammasome activation. The omega-3 fatty EPA is known to suppress palmitate-induced metabolic stress, and when combining palmitate and EPA, we found markedly reduced release of IL-1β. By viewing CF stained with Bodipy under fluorescence microscopy, we observed an inhibitory effect of EPA on PA-induced lipid accumulation. AMP-activated protein kinase (AMPK) is a central regulator of cellular energy homeostasis and also suppresses reactive oxygen species (ROS) production. We found that palmitate markedly reduced AMPK phosphorylation and Mitosox staining revealed increased mitochondrial ROS. Addition of the pharmacological AMPK activator AICAR completely blocked palmitate-induced IL-1β production. AMPK is also involved in regulation of autophagy, and we found that palmitate reduced levels of beclin-1, indicating that reduced autophagy could represent a mechanism for palmitate-induced inflammasome activation. Conclusion: Palmitate causes activation of the NLRP3 inflammasome in cardiac fibroblasts and this may involve increased mitochondrial ROS and defective autophagy. These findings indicate that NLRP3 inflammasome may act as a sensor of metabolic stress in the heart. EPA inhibits PA-induced NLRP3 inflammasome activation, possibly via reduced lipid accumulation.